Consumption of foods rich in antioxidants in outpatients with diabetic retinopathy at Hospital La Carlota during 2021: Consumo de alimentos ricos en antioxidantes en pacientes ambulatorios con retinopatía diabética del Hospital La Carlota durante el 2021 - Martínez de Kurata, Raquel (2023)
The objective of this work was to assess the quality of the consumption of foods rich in antioxidants such as vitamin C, E and selenium, in a sample of 28 patients with diabetic retinopathy (DR) who attended outpatient consultation at the Institute of Vision, of the La Carlota Hospital, in February 2021. The research was observational, descriptive, cross-sectional, with an analytical component. Patients older than 20 years with DR were included, who agreed to participate in the food survey applied by hospital professionals. Sociodemographic and ophthalmological variables and food consumption were measured. Results: 60% of the cases were men, the mean age was 56 ± 13 years. Proliferative diabetic retinopathy (PDR) was the most frequent diagnosis. Regarding food consumption, the most frequently mentioned were eggs, onion, garlic, parsley, orange, banana, lemon, corn tortillas, chili peppers, avocado. It was almost zero intake of whole fiber, nuts and vegetable oils. The median consumption of vitamin C was 87.5 mg, vitamin E 13.9 mg, and selenium 36.7 mcg. Deficient consumption of these micronutrients was found in 63% of cases, especially in men. In this research, no statistically significant association was found between poor consumption of foods rich in antioxidants and PDR (X2 p= 0.2). Conclusion: There is a marked deficit in the consumption of foods with a high contribution of antioxidants in patients with RD, but this situation does not affect the severity of the disease.